143k views
2 votes
Can y’all please help meeeee
i would really appreciate it :)

Can y’all please help meeeee i would really appreciate it :)-example-1
User Rodriguez
by
5.0k points

2 Answers

3 votes

Answer:


f^(-1)(x) = (x - 2)² - 6

Explanation:

let y = f(x) and rearrange making x the subject, that is

y =
√(x+6) + 2 ( subtract 2 from both sides )

y - 2 =
√(x+6) ( square both sides )

(y - 2)² = x + 6 ( subtract 6 from both sides )

(y - 2)² - 6 = x

Change y back into terms of x with x =
f^(-1)(x) , thus


f^(-1)(x) = (x - 2)² - 6

User Blue Raspberry
by
4.7k points
3 votes

Answer:

its 10

Explanation:

User Hattenn
by
4.9k points